2009
DOI: 10.1016/j.cell.2009.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Translesion Synthesis by DNA Pol II

Abstract: Summary E. coli DNA Pol II and eukaryotic Rev3 are B-family polymerases that can extend primers past a damaged or mismatched site when the high-fidelity replicative polymerases in the same family are ineffective. We report here the biochemical and structural properties of DNA Pol II that facilitate this translesion synthesis. DNA Pol II can extend primers past lesions either directly or by template skipping, in which small protein cavities outside of the active site accommodate looped-out template nucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
143
6
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 55 publications
3
143
6
3
Order By: Relevance
“…To validate the reaction-ready nature of this structure, we measured the extension efficiency of the T:G mispair in solution by Pol η and showed that the catalytic efficiency (k cat /K M ) is reduced by 32-fold compared with normal DNA synthesis (Table S1). Pol η is thus more efficient in primer extension after a mismatched base pair than replicative and Bfamily TLS polymerases, whose catalytic efficiency is reduced by 10,000 and 100 folds, respectively (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the reaction-ready nature of this structure, we measured the extension efficiency of the T:G mispair in solution by Pol η and showed that the catalytic efficiency (k cat /K M ) is reduced by 32-fold compared with normal DNA synthesis (Table S1). Pol η is thus more efficient in primer extension after a mismatched base pair than replicative and Bfamily TLS polymerases, whose catalytic efficiency is reduced by 10,000 and 100 folds, respectively (32).…”
Section: Resultsmentioning
confidence: 99%
“…For the A-to-G mutation to persist in somatic cells, it is necessary that the DNA primer be extended after the mismatch during the short-patch DNA synthesis to prevent the misinserted G from being removed by the editing function of a replicative polymerase. Most polymerases are inefficient in mismatch extension (32). To extend a T:G mismatch, both the translocation step and the primer extension step are examined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because hTHG1 shares no significant sequence similarity with any known protein, it was unclear whether hTHG1 would have any structural homologs. Surprisingly, significant homology was found with guanylyl and adenylyl cyclases [βαββαβ motif of C 1a domain; Z score ¼ 8.0; Protein Data Bank (PDB) ID codes 2W01 (21) and 3E8A (22)] (23), along with the palm domain of several traditional polymerases including T7 DNA polymerase, a family A polymerase [ Z score ¼ 5.3, PDB ID code 1T7P (24)], and DNA polymerase II, a member of the B family [Z score ¼ 5.9, PDB ID code 1Q8I, (25)]. The fold of the hTHG1 βαββαβ motif (residues 22-135) most closely matches that of the cyclases.…”
Section: Resultsmentioning
confidence: 99%
“…For example, interactions between PCNA and DNAP from Pyrococcus furiousos appear to decrease the binding of primer strands at the exo site and stabilize the P/T DNA duplex within the polymerase, thereby favoring processive elongation (26). In addition, partitioning of the primer terminus between the polymerase and exonuclease active sites modulates translesion synthesis by E. coli DNA Pol II (27). Polymerase features that are involved in control of the occupancy of the exo site are beginning to be investigated by protein engineering (27).…”
Section: A B C D Ementioning
confidence: 99%
“…In addition, partitioning of the primer terminus between the polymerase and exonuclease active sites modulates translesion synthesis by E. coli DNA Pol II (27). Polymerase features that are involved in control of the occupancy of the exo site are beginning to be investigated by protein engineering (27). Not all DNA polymerases have an exo binding mode; repair polymerases in the X and Y families and certain A-family polymerases that perform translesion and mutagenic DNA synthesis lack proofreading exonuclease activity (28).…”
Section: A B C D Ementioning
confidence: 99%